Il ricettario veneziano del ms. MA 400 della Biblioteca Civica “A. Mai” di Bergamo (cc. 66r-98v) - Lemme, Claudia (Quaderni Veneti)
This article aims to provide a first edition of an unpublished medical recipe book included in ms. Bergamo, Biblioteca civica “Angelo Mai”, MA 400 (ff. 66r-98v). The text, mainly written in fifteenth century venetian variety with a small presence of Latin, is intended to implement the medical repertories now available in corpora and placeable in the Veneto region, such as Corpus ReMediA (http://remediaweb.ovi.cnr.it/) and Corpus VEV (http://vevweb.ovi.cnr.it/). The author provides an integral edition of the medical text accompanied by lexicographical and philological notes and a brief linguistic analysis.